EFEK DIGITALISASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Syakir Syabiansah, Farhan (Center for Economic Studies Universitas Katolik Parahyangan, 2025)
This study examines the impact of digitalization on Indonesia's economic growth from 2000 to 2022 using the Ordinary Least Squares (OLS) method. The research includes variables such as the digitalization index, labor force participation, foreign direct investment (FDI), domestic investment (DI), and education (mean years of schooling). The findings reveal that digitalization and FDI significantly and positively affect Indonesia's GDP, indicating the pivotal role of technology adoption and international capital flows in economic expansion. Conversely, education exhibits a significant negative effect, suggesting possibly indicating a mismatch between educational output and labor market needs. Meanwhile, labor force participation and domestic investment show no significant effect on growth. These results highlight the need for strategic improvements in digital infrastructure, educational quality, and investment policy to enhance the inclusiveness and sustainability of economic development in the digital era. The study concludes that while digitalization and FDI are key drivers of growth, optimizing their benefits requires coordinated policy support, particularly in workforce development and local investment ecosystems.